Examining dental students' performance in multiple-choice questions and pre-clinical practical exams in fixed prosthodontics: Gender differences, stress, and confidence - Seham Elsawaay; Ahmed Mhanni; Abubaker Qutieshat (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: In dental education, understanding optimal assessment methods and factors like stress and confidence is essential. This research assessed second-year dental students' performance in fixed prosthodontics using multiple-choice questions (MCQs) and pre-clinical practical exams, examining impacts of gender, stress, and confidence. Materials & Methods: Using a quasi-experimental design, 495 students from a single faculty underwent assessment. Selected via convenience sampling, they were exposed to MCQs and practical exams in fixed prosthodontics. An expert-reviewed questionnaire gauged their stress and confidence. Data was analyzed using descriptive statistics, t-tests, and Pearson's correlation. Additionally, a balanced sub-set of 176 students (88 males and 88 females) was chosen for gender-based analysis. Results: Findings indicate statistical parity between MCQ and practical exam performances (p>0.001). Females slightly outperformed in MCQs, while males excelled in practicals, without reaching statistical significance (p>0.05). Stress correlated with practical exam outcomes (r=0.34, p=0.001), and confidence with MCQ scores (r=0.41, p<0.0001). Conclusion: The research underscores near-equivalence of MCQs and practical exams for student assessments in fixed prosthodontics. Recognizing the roles of stress and confidence in assessments offers insights for balanced evaluations. Dental faculties should integrate these findings, and future work should pivot towards tool validations for enriched learning.